A novel interpretation of fatigue delamination growth behavior in CFRP multidirectional laminates. (14th September 2016) - Zhao, Libin; Gong, Yu; Zhang, Jianyu; Wang, Yana; Lu, Zizi; Peng, Lei; Hu, Ning
Abstract: Two Paris-type models are proposed to characterize the fatigue delamination growth (FDG) behavior in CFRP laminates. The crack-driving forces denoted by two definitions of the strain energy release rate (SERR) range against the fatigue delamination resistance of composite materials are introduced to control the FDG. The first definition is the square of the difference between the square root of maximum SERR and that of minimum SERR. The second one is the arithmetic difference between the maximum and minimum SERR. A series of fatigue delamination tests of CFRP multidirectional laminates under various stress ratios and mode-mixity ratios were carried out. Among different Paris relations, the FDG rate corrected by the first model exhibits a linear relationship with R -ratio dependency, and the second model further removes the R -ratio dependence, under different mode-mixity ratios, on a log-log scale. The experimental results indicate that the presented models can provide more generic descriptions and a proper interpretation of the FDG behavior in CFRP multidirectional laminates.